Isolation and caracterization of ficin enzyme from Ficus septica Burm F stem latex - Sri Wahyuni; R. Susanti; Retno Sri Iswari (Indonesian Journal of Biotechnology, 2015)
This research aims to isolate and characterize the fcin enzyme from Ficus septica stem latex. Ficin from Ficus septica stem latex was isolated using column chromatography. Then enzyme activity was tested at different temperature (40oC, 50oC, 60oC, 70oC) and pH (6.0, 7.0, 8.0) levels. Ficin enzyme activity of joint treatment with variations in temperature and pH was analyzed using two-way ANOVA with a factorial pattern followed by Least Signifcant Difference (LSD) test. The results showed that temperature treatment signifcantly affects enzyme activity. However, the treatment of pH and the interaction between temperature and pH did not signifcantly affect the fcin enzyme activity. There was no signifcant difference in fcin activity at the incubation temperatures of 40oC and 50oC, as well as 60oC and 70oC. However, comparing the incubation temperatures of 40oC and 50oC with treatment 60°C and 70°C showed a signifcant difference in fcin enzyme activity. In the treatment of incubation at pH 6, 7 and 8 for fcin enzyme activity showed no signifcant difference. We concluded that the Ficus septica plant latex contained fcin enzyme with an optimum temperature of 60°C and optimum pH of 6, 7, and 8.